2008
DOI: 10.1016/j.berh.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Capillaroscopy

Abstract: Capillaroscopy is the most reliable way to distinguish between primary and secondary Raynaud's phenomenon (RP) through identification of an early pattern of systemic sclerosis (SSc). The presence of giant capillaries and microhaemorrhages on nailfold videocapillaroscopy (NVC) is sufficient to identify the scleroderma pattern (early), and an increase in these features and the addition of loss of capillaries (active pattern) is followed by neo-angiogenesis, fibrosis and 'desertification' (late pattern). The sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 28 publications
3
120
2
12
Order By: Relevance
“…Score for irregularly enlarged capillaries, capillaries loss, disorganization of the microvascular array and capillary ramifications were found to have increased, while scores for giant capillaries and hemorrhages decreased during follow-up. A 4% variability was found in the score assessment by the different evaluators [43], [44] and [45].…”
Section: Secondary Rpmentioning
confidence: 93%
“…Score for irregularly enlarged capillaries, capillaries loss, disorganization of the microvascular array and capillary ramifications were found to have increased, while scores for giant capillaries and hemorrhages decreased during follow-up. A 4% variability was found in the score assessment by the different evaluators [43], [44] and [45].…”
Section: Secondary Rpmentioning
confidence: 93%
“…The frequency of hemorrhages is significantly higher in the fourth fingers than in the other fingers with naked eyes [23]. The most accurate morphological assessment with dermatoscope is commonly performed on the fourth and fifth fingers, because of the greater transparency of the skin on these fingers [6]. Consistent with this, the frequency of enlarged capillaries and hemorrhages was the highest in the fourth fingers from SSc patients.…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested that enlarged capillaries represent a local autoregulatory response to tissue hypoxia [5]. The dilation may represent the first sign of vessel wall damage, and the increased red color is related to the greater number of red blood cells [6]. Local hemorrhages is also linked to the damage of the vessel wall [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations